Relating movement markers of schizophrenia to self-experience: a mixed-methods study - Martin, Lily; Melchert, David; Knack, Monika; Fuchs, Thomas (Frontiers in psychiatry, 2023)
IntroductionBasic self-disorders on the one hand and motor symptoms on the other hand are discussed as endophenotypes of schizophrenia psychopathology. However, the systematic interaction between motor symptoms and the self-experience of patients is rarely studied.MethodsIn a previous study we defined motor markers of schizophrenia via a data-driven analysis of patients' gait patterns. In this study, we related the movement markers to measures of basic self-disorder obtained with EASE interviews. We substantiated the correlations with a qualitative content analysis of the interviews of a subset of four patients. We related qualitative and quantitative data on an intra- and interpersonal level.ResultsOur results suggest an association between the previously defined, theory-independent movement markers and basic self-disorders, specifically in the domain of cognition, self-experience and bodily experiences. While movement marker manifestation was not precisely reflected in the individuals' descriptions of anomalous self- and body experience, we found clear trends of more and more intense descriptions with increasing movement marker scores, when looking at specific experiences, such as hyper reflexivity.DiscussionThese results foster an integrated view of the patient and could stimulate therapeutic approaches aiming at an improvement of self- and body-experience of patients with schizophrenia.